CLINICAL STUDY ON SILENT MYOCARDIAL ISCHEMIA - TAMURA, Yoshiyuki; MIZUNUMA, Yoshiyuki; NAGASE, Norio; ISHIMOTO, Takeo; SAKO, Harunobu; KOBAYASHI, Kazuo; MORI, Kenichi; OKUMURA, Hironobu; KAWAGUCHI, Takashi (Japanese Journal of National Medical Services, 1993)
Attacks of myocardial ischemia without any symptoms are termed as silent myocardial ischemia (SMI). We studied the incidence of attacks and arrhythmias in 87 patients of SMI demonstrated on 24-hour electrocardiographic (Holter) monitoring. SMI patients were demonstrated in 3 groups by Cohn's report: type I; those totally asymptomatic (9 cases), type II; those after myocardial infarction (9 cases) and type III; those with angina pectoris (65 cases). The frequencies of SMI events on 24-hour Holter monitoring were as follows; one, from 2 to 4 and more than 5 times were 25 (30%), 46 (55%) and 12 cases (15%), respectively. The episodes of SMI occurred predominantly during the daytime hours; from 6:00am to 0:00pm and from 0:00pm to 6:00pm were 40% and 30%, respectively. At event time of SMI (44 events) sinus tachycardia, ventricular premature contractions (VPCs) and atrial fibrillation were found in 21 (48%), 4 (9%) and 1 event (2%), respectively. Incidences of VPCs for 24 hours of type I, II and III were 100, 78 and 69%, respectively and the greater part of VPCs was more than Lown's grade 3. Sixty-seven patients of SMI (7 for type I, 8 for type II and 52 for type III) were followed up for from 1.1 to 3.3 years (mean 2.4 years). Eleven (16.4%) died and of those patients, five (7.5%) were cardiac death (2 for type II and 3 for type III) . Four (6%) developed myocardial infarction (1 for type II and 3 for type III). Thus, patients with SMI had high incidences of arrhythmias and cardiac events.